2021
DOI: 10.1017/s0022215121000074
|View full text |Cite
|
Sign up to set email alerts
|

Do patients report quality of life improvements after fitting of their unilateral bone conducting hearing implant?

Abstract: Objective The audiological benefits of a bone conducting hearing implant are well documented; however, there is a paucity of literature comparing pre- and post-operative quality of life benefits. This study assessed the quality of life status before and after the device is implanted. Methods A prospective study was conducted of all adult bone conducting hearing implants inserted in a teaching hospital between 2012 and 2017. All patients completed the Glasgow Health Status Inventory, a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In line with our findings, Meghji et al found significantly improved GHSI total and general scores after surgery (23). Interestingly, in their study, the physical health score also increased postoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our findings, Meghji et al found significantly improved GHSI total and general scores after surgery (23). Interestingly, in their study, the physical health score also increased postoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…Health-Related Quality of Life Many studies have shown clinical advantages of the adapted surgical techniques, but there is only little known about the change in patients' HRQoL (16,32,33). This multidomain evaluation of the HRQoL informs about the impact of our primary and secondary outcomes on a patient's functioning in their daily life.…”
Section: Bia400 Versus Ponto Widementioning
confidence: 99%